Arquivos legislativos: a política pública arquivistica em instituições legislativas municipais - Wendell Lopes de Assis (2015)
Brazil has 5,565 municipalities, each of which has a town hall. In the 2012 elections, he was elected a total of 57,430 (fifty-seven thousand four hundred thirty) councilors for these legislative houses. The main function of a councilor is to draft laws, which materialize in the documents. Collections of the files of these institutions are records of collective memory. A community that no longer has such collections loses muchsocial capacity building of a collective identity. Considering the large production of documents, the high number of legislative houses and the National Archives Policy, the study aimed to identify the roles and archiving situation of legislative bodies of the municipalities that are state capitals and the Federal District; raise the necessary data to assess the files in these policy Legislative Houses; and discuss ways to implement a public policy file these institutions. Exploratory methodological nature,the survey was conducted from the application of a questionnaire, based on the Census 2005 Legislative Interlegis, and analysis of the minutes of the plenary meetings of the National Council on Archives. Regarding functions of city councils, it was found that they are similar; the National Archives should be more solid in their actions; and that public policy document management can be an outlet for the preservation of memory and access to their documents.